Moving from discourse to Praxis: Situating academics at the centre of decolonisation struggle: - Sibiya, A. T.; Ndaba, M. (South African Journal of Higher Education, 2023)
As part of contributing to the decolonisation debate to reclaim and re-purpose the universities as public good institutions, drawing from Freire’s notion of praxis we argue that there is a need to move from theorisation of concepts or what we refer to as discourses to praxis, and academics must drive the decolonisation project. Unlike students, academics have immense power to influence choices of pedagogical approaches, processes of curriculum design, and knowledge production. Academics enjoy academic freedom. This implies that they have the freedom to teach and conduct research without external control in their area of expertise, which gives them special protection within the classroom and the parameters of their field of expert knowledge. Thus, we argue that the freedom that academics enjoy puts them in a good position to be drivers of the project of decolonising higher education. As key role players on processes of teaching and learning as well as knowledge production in higher education, they have some degree of power that they are better positioned to drive the decolonial project. They can use their roles as teachers and researchers to advance the decolonisation agenda.